Adoption of Low Cost Technologies for Improving the Productivity of Sugarcane in Visakhapatnam District of Andhra Pradesh - Srinivas, Manukonda; Rao, C. V. Rama; Anusha, B.; Saritha, R.; Reddy, A. Vishnuvardhan (International Journal of Economic Plants, 2017)
Sugarcane cultivation in Visakhapatnam district is confined to rainfall dependent with little tankfed situation under low fertile red loamy soils. Out of 37,865 ha of sugarcane cultivation 65% of area is under complete rainfed cultivation. The productivity of sugarcane in Visakhapatnam district was very low as compared to other sugarcane growing districts in the state because of certain weather constraints viz., continuous moisture stress, frequent prolonged dry spells and waterlogged conditions in rainy season besides poor transfer of technology. Based on those constraints on-farm demonstrations, skill demonstrations and training programmes were conducted by ANGR Agricultural University extension wing, DAATT Centre, Visakhapatnam continuously from 2001 to 2011 years on various agro-techniques which are really effective and economical for sugarcane farmers. The results revealed that productivity of sugarcane was increased to 29.7% by timely pocketing of recommended nutrients and 38.8% by using drought resistant varieties under rainfed situations. The good agricultural management practices increased the cane yield by 36% and timely control of smut disease with propiconazole increase live cane number which in turn increased the cane yield up to 34.8%. Farmers of Visakhapatnam are reaping an additional income of INR 2125.0 to INR 5000.0 by adopting paired row planting and intercropped with pulses or vegetables in sugarcane against sole sugarcane cultivation. It clearly indicates that, cane yield of sugarcane can be increased from 51 t ha-1 to 81 t ha-1 by adopting appropriate management practices by duly considering the climate conditions with efficient transfer of technology.